Tingkat Pengetahuan Osteoporosis Sekunder dan Perilaku Pencegahan Mahasiswa Universitas Malahayati - Nopi Sani; Yuniastini Yuniastini; Aswedi Putra; Yuliyana Yuliyana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Osteoporosis occurs due to the body's inability to regulate mineral content in the bones and will interfere with the process of bone metabolism. signs and symptoms of osteoporosis are called hidden killers (silent disease). Research Objectives: To determine the relationship between the level of knowledge of secondary osteoporosis with secondary osteoporosis prevention behavior in students at Malahayati University 2019. Research Method: This research is an analytic survey research using a cross-sectional design. The sampling technique is simple random sampling. The number of samples was 76 respondents, the data were analyzed using the Spearman test. The research instrument was in the form of a questionnaire. Results: The study found that the highest level of knowledge distribution was good knowledge as many as 62 respondents (81.6%) and distribution of prevention behaviors most of the good behaviors were 50 respondents (65.8%). Spearman's statistical test results showed a relationship with the results of p = 0.001 (p 0.1). Conclusion: There is a relationship between the level of knowledge with preventative behavior about secondary osteoporosis